Разработка программного средства по оценке доз облучения и прогнозу радиационного риска в аварийной ситуации - Kryuk, Юлианна; Kunets, И. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The need at the use of the information system for the rise in a radiological emergency preparedness was considered. The mathematic models of personnel and population exposure dose assessments in different types of emergency situations were given. The visual model of program product has been created by used the object-oriented methodology with applying the notations of the unified modeling language for the automation of workers and population dose assessment and health risk prognosis in different emergency situations connected with radiation source.